Framing Dedi Mulyadi's Vasectomy Policy in International Media: A Comparative Analysis Using Entman's Framing Theory and Its Implications for Indonesia's Public Diplomacy - Tris Dina Susanti; Atef Fahrudin (INJECT (Interdisciplinary Journal of Communication), 2025)
This study examines the international media's portrayal of the vasectomy policy as a prerequisite for accessing social assistance, as proposed by West Java Governor Dedi Mulyadi. Using Robert Entman's theoretical framework, this research examines how three international media outlets (Channel News Asia, South China Morning Post, and The Telegraph) frame this controversial policy through four key elements: problem definition, causal interpretation, moral evaluation, and treatment recommendation. The research method employs qualitative framing analysis with a systematic approach to the news corpus from the three media outlets. Results indicate that all three media outlets use negative framing with a dominance of moral evaluation (90%) and problem definition (85%), yet with different strategies: SCMP uses a "discriminatory policy" frame (9/10), Telegraph emphasizes "human rights violation" (8/10), and CNA employs a "governance problem" approach (7/10). Differences in intensity and editorial tone reflect the geographical and ideological orientations of each media outlet, with the SCMP being the most critical, the Telegraph focusing on international human rights standards, and CNA adopting a more contextual approach to the complexities of Southeast Asia. This study confirms the relevance of Entman's theory in the digital era and reveals that treatment recommendation is the most diverse element in international framing. These findings offer strategic implications for Indonesia's public diplomacy, suggesting the development of targeted and proactive communication strategies in response to the evolving global media landscape.